Association Between Cardiovascular Diseases and Lingual Varices: A Systematic Review and Meta-Analysis - Aya El Kanfoud-Ezzarraa; Sonia Egido-Moreno; Ani Mantinyan-Hakobyan; Mónica Blázquez Hinarejos; Beatriz González-Navarro; Anna Oliveras Serrano; Eva Otero-Rey; José López-López (Journal of Clinical Medicine, 2026)
Background/Objectives: Cardiovascular diseases (CVD) remain the leading cause of mortality worldwide. Early identification of individuals at risk is essential to reduce disease burden. Lingual varices (LV), a common oral vascular condition, have been suggested as a potential non-invasive clinical marker of systemic vascular alterations. This study aimed to evaluate the association between lingual varices and cardiovascular diseases through a systematic review and meta-analysis. Methods: A systematic review was conducted according to PRISMA guidelines and Cochrane recommendations and registered in PROSPERO (CRD420251172737). Electronic searches were performed in PubMed, Web of Science, and Scopus databases. Observational studies assessing the association between lingual varices and cardiovascular diseases in adults were included. Odds ratios (OR) with 95% confidence intervals (CI) were calculated, and meta-analysis was performed using fixed- or random-effects models depending on heterogeneity. Results: Thirteen studies involving 6322 participants were included. The overall prevalence of lingual varices was 34.8%. The meta-analysis demonstrated a significant association between lingual varices and cardiovascular disease (OR = 4.54; 95% CI: 3.35–6.17). Among the cardiovascular conditions evaluated, hypertension also showed a significant association with lingual varices (OR = 4.14; 95% CI: 1.66–10.29). Lingual varices were also significantly associated with smoking (OR = 3.06; 95% CI: 1.61–5.82) and lower extremity varicose veins (OR = 1.64; 95% CI: 1.04–2.58). No significant association was observed with sex (OR = 0.95; 95% CI: 0.67–1.34; p = 0.77). Conclusions: Lingual varices are significantly associated with cardiovascular disease. Although they may represent a readily identifiable oral finding associated with cardiovascular risk profile, the available evidence does not support their use as an independent screening or diagnostic marker. Further prospective studies are required to determine their predictive value and clinical utility.